2002
DOI: 10.1590/s0073-47212002000300005
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del herbicida Paraquat sobre el zooplancton

Abstract: EFFECTS OF PARAQUAT HERBICIDE ON ZOOPLANKTON. The effects of 0.1; 0.2; 0.4 and 0.8 mlPQ/L were analized on a zooplankton community, to determine the most sensitive species and to analize the occurence of physical abnormalities. A total of 40 taxa were determined. Paraquat affected significantly the zooplankton density but not the species richness. A progressive state of deformation of these organisms was also observed. Paraquat showed to be highly toxic for the zooplankton, so this herbicide should be strictly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…According to GAGNETEN (2002), herbicides can provoke zooplankton density reduction, especially among herbivorous crustaceans (Cladocers and Copepods), determine feeding decrease and algae community structure exchanges, presenting toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…According to GAGNETEN (2002), herbicides can provoke zooplankton density reduction, especially among herbivorous crustaceans (Cladocers and Copepods), determine feeding decrease and algae community structure exchanges, presenting toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…This possible influence was also recorded by Reimche et al (2008), where the cladoceran assemblage showed a density variation caused by the stress of the application of this herbicide. The use of pesticides reduces the availability of food for the benthic macroinvertebrates and changes the structure of the algae community, and the toxic effect on these food resources may also be associated with this (Gagneten, 2002). Some studies have suggested the possibility that the toxic agents to non-target organisms, in the case of herbicides, are the adjuvants and the surfactants used in the commercial formulation of each pesticide (Tatum 2004;Kitulagodage et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these organisms are frequently employed in ecotoxicologic assays since they are one of the most sensitive groups to the effects of toxic chemical products, as well as they are in a central position in the lentic food chain (HANAZATO, 2001;GAGNETEN, 2002).…”
Section: Introductionmentioning
confidence: 99%